(untitled) (Universitas Medica, 2021)
Introduction: The strategy of Integrated Management of Childhood Illness (IMCI) reduces the morbidity and mortality of children under 5 years of age. Clinical IMCI evaluates the child integrally, identifies frequent pathologies, classifies by severity and intervenes. Knowing experiences of the teaching-learning process is essential to improve. Methods: A systematic review of articles was carried out until January 30, 2021. Selected studies had to compared two or more teaching strategies of clinical IMCI or before and after the training. Results: Ten studies were found, four compared knowledge before and after training, five analyzed two different teaching methods and one was a systematic review that compared long vs. short course. There is heterogeneity in the didactic strategies and in the evaluation of learning, so a quantitative synthesis could not be carried out. Virtual teaching has cost advantages. Theory together with supervised practical activities improve the competences obtained. Conclusions: Contextualizing clinical IMCI is important. It is suggested to create a homogeneous strategy to have a universal reference, define the corrective, the aspects that do not need to be modified and evaluate in the long term which concepts should be reinforced